Comparison of Oral Hygiene Attitudes, Awareness and Periodontal Parameters of Undergraduate Dental Students - Emine Pırım Gorgun; Aysan Lektemur Alpan (Cumhuriyet Dental Journal, 2019)
Objectives:  The aim of this study was to compare the differences in self-reported oral health attitudes and clinical measurements between dental students who enrolled in or not enrolled in periodontology course in Turkey.